The effects of plyometric vs. dynamic stabilization and balance training on power, balance, and landing force in female athletes - Myer, G. D.; Ford, K. R.; Brent, J. L.; Hewett, T. E. (The Journal of Strength and Conditioning Research, 2006)
Neuromuscular training protocols that include both plyometrics and dynamic balance exercises can significantly improve biomechanics and neuromuscular performance and reduce anterior cruciate ligament injury risk in female athletes. The purpose of this study was to compare the effects of plyometrics (PLYO) versus dynamic stabilization and balance training (BAL) on power, balance, strength, and landing force in female athletes. Either PLYO or BAL were included as a component of a dynamic neuromuscular training regimen that reduced measures related to ACL injury and increased measures of performance. Nineteen high school female athletes participated in training 3 times a week for 7 weeks. The PLYO (n = 8) group did not receive any dynamic balance exercises and the BAL (n = 11) group did not receive any maximum effort jumps during training. Pretraining vs. posttraining measures of impact force and standard deviation of center of pressure (COP) were recorded during a single leg hop and hold. Subjects were also tested for training effects in strength (isokinetic and isoinertial) and power (vertical jump). The percent change from pretest to posttest in vertical ground reaction force was significantly different between the BAL and PLYO groups on the dominant side (p < 0.05). Both groups decreased their standard deviation of center of pressure (COP) during hop landings in the medial/lateral direction on their dominant side, which equalized pretested side to side differences. Both groups increased hamstrings strength and vertical jump. The results of this study suggest that both PLYO and BAL training are effective at increasing measures of neuromuscular power and control. A combination of PLYO and BAL training may further maximize the effectiveness of preseason training for female athletes.